2020
DOI: 10.1039/d0mt00209g
|View full text |Cite
|
Sign up to set email alerts
|

FRA1 is essential for the maintenance of the oncogenic phenotype induced by in vitro long-term arsenic exposure

Abstract: Arsenic induces oncogenic effects activating stress-related signalling pathways. This can result in the over-activation of the AP-1 protein, specifically its FRA1 component. FRA1 is a transcription factor frequently overexpressed in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…MEF cells, knockdown for different genes, have shown their usefulness to discover mechanisms involved in oncogenesis. This occurs with FRA1, a transcription factor frequently overexpressed in epithelial tumors, playing an essential role in the in vitro cell transformation induced by arsenic (Barguilla et al, 2020); or with the Atg5 (autophagy-related gene 5) knockdown, playing a role on the levels of inflammation-related proteins and apoptosis induced by polystyrene nanoplastics (Wang et al, 2021). In the present study, PTP cells have been shown to dramatically accumulate large amounts of polystyrene nanoplastics, mainly after exposures lasting for 48 h. This easy uptake reaffirms the usefulness of our selected cell model to evaluate the effects of MNPLs.…”
Section: Discussionmentioning
confidence: 99%
“…MEF cells, knockdown for different genes, have shown their usefulness to discover mechanisms involved in oncogenesis. This occurs with FRA1, a transcription factor frequently overexpressed in epithelial tumors, playing an essential role in the in vitro cell transformation induced by arsenic (Barguilla et al, 2020); or with the Atg5 (autophagy-related gene 5) knockdown, playing a role on the levels of inflammation-related proteins and apoptosis induced by polystyrene nanoplastics (Wang et al, 2021). In the present study, PTP cells have been shown to dramatically accumulate large amounts of polystyrene nanoplastics, mainly after exposures lasting for 48 h. This easy uptake reaffirms the usefulness of our selected cell model to evaluate the effects of MNPLs.…”
Section: Discussionmentioning
confidence: 99%
“…The EMT mechanism cannot only make PGCCs manifest the relevant features of tumor stem cells but can also be part of the cause of the metastasis of tumor cells, thereby linking stemness and metastasis in PGCCs [ 82 , 83 ]. Overexpression of FRA-1 (encoded by the FOSL1 gene), a leucine zipper protein forming the transcription factor complex AP-1, can promote tumor dissemination due to its possible role in EMT-like processes, and metastatic spreading, by driving the expression of EMT-inducing transcription factors, cytokines, and microRNAs [ 3 , 4 , 18 , 84 ]. Hence, we tested FRA-1 expression levels after exposure to different doses of X-ray irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Our effort to define the molecular signatures of IR-induced modulation of UJT corroborates the recent observations that the EMT/pEMT and UJT are quite different processes [ 103 ]. Even the overexpression of FRA-1 can promote tumor dissemination due to its possible role in EMT-like processes and metastatic spreading [ 3 , 4 , 18 , 84 ], but it does not likely play a role in tested GBM cells as indicated by unaltered IR-stress-induced FRA-1 expression in irradiated compared to non-irradiated GBM cells irrespectively of their PTEN status ( Figure 8 d). These results suggest a possible role of other transcription factor(s) (such as Twist, Snail, ZEB-1/2) in maintenance of dormancy (quiescence and/or SIPS) and cancer stem-like phenotypes of human GBM cells in response to IR exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decreasing trend was the same as the trend observed in the tissues of the group orally injected with the control drugs (Dexa [5 mg/kg] or RT [40 mg/kg]) used in the experiments ( Figure 3 e–f). Additionally, the phosphorylation level of p38, known as an upstream player of FRA-1 [ 33 ], was also reduced by Pd-EE from 5 to 30 min after LPS treatment ( Figure 3 g). Hereby, it was demonstrated that Pd-EE affects the activities of inflammation-regulatory transcription factors.…”
Section: Resultsmentioning
confidence: 99%